Real-World Outcomes of Revascularization Strategies in Patients With Left Ventricular Dysfunction and Three-Vessel Coronary Disease Stratified by Mitral Regurgitation - Fan, Qin; Liu, Jun; Xu, Yan; Ni, Ruiqing; Xi, Rui; Wang, Fang; Hu, Jian; Sun, Hongyue; Yang, Zhenkun; Zhou, Mi; Zhang, Ruiyan; Zhao, Qiang; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: Limited information exists regarding optimal revascularization options for patients with triple-vessel coronary artery disease (TVD), heart failure (HF) and different degrees of mitral regurgitation (MR). Thus, we aimed to compare the effect of percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) surgery in the indicated patients. Methods and results: In the real-world prospective study, 1190 patients with multi-vessel and decreased left ventricular systolic function but without severe MR, who underwent PCI or CABG, were enrolled and followed-up for 4.7±1.8 years. The primary endpoint was a composite of cardiovascular death and HF hospitalization. Secondary endpoints were the individual components of the primary outcome. Risk of the primary endpoint was higher in the PCI than in the CABG group (HR 1.38, 95%CI 1.14-1.67, P <0.01), particularly in patients with moderate MR (HR 1.85, 95%CI 1.35-2.55, P <0.01). In patients with no-mild MR, the risk of the primary endpoint did not differ significantly between PCI and CABG (P =0.09). Treatment with PCI was associated with an increased risk for cardiovascular death and HF hospitalization in the moderate MR cohort, while PCI was comparable to CABG in the no-mild MR cohort. Conclusions: In this real-world study, for patients with HF and TVD, CABG was related to lower adverse outcome rates compared to PCI. Assessment of MR can aid in selecting optimal revascularization therapies and in risk stratification.